Environmental governance of solid waste management in municipalities of Oaxaca, Mexico - Juárez de la Rosa, Jair; Medina Martínez, Haidi; Taboada González, Paul; Aguilar Virgen, Quetzalli; Márquez Benavides, Liliana (Acta Universitaria, 2023)
In Mexico, municipal governments are responsible for managing municipal solid waste (MSW). For these municipalities there is not an established scheme of parameters that is useful for estimating environmental governance in waste management. The state of Oaxaca is a federal entity with a significant lag in education and standard of living; it has 570 municipalities organized in eight regions. The objective was to generate a mapping that evaluates the status of MSW management in the municipalities of this entity, through a base of indicators. The results of the evaluation were low for 82% of the municipalities, while the only region with a passing evaluation was the Isthmus (28 points). In addition, a baseline of parameters that estimates environmental governance in waste management and is useful in other similar studies was proposed.